Whole body magnetic resonance angiography and computed tomography angiography in the vascular mapping of head and neck: an intraindividual comparison - Kramer, Manuel; Schwab, Siegfried; Nkenke, Emeka; Eller, Achim; Kammerer, Ferdinand; May, Matthias; Baigger, Joao F.; Uder, Michael; Lell, Michael (Head & Face Medicine, 2014)
The aim of the study was to compare the detectability of neck vessels with contrast enhanced magnetic resonance angiography (MRA) in the setting of a whole-body MRA and multislice computed tomography angiography (CTA) for preoperative vascular mapping of head and neck.In 20 patients MRA was performed prior to microvascular reconstruction of the mandible with osteomyocutaneous flaps. CTA of the neck served as the method of reference.1.5 T contrast enhanced magnetic resonance angiograms were acquired to visualize the vascular structures of the neck in the setting of a whole-body MRA examination. 64-slice spiral computed tomography was performed with a dual-phase protocol, using the arterial phase images for 3D CTA reconstruction. Maximum intensity projection was employed to visualize MRA and CTA data. To retrieve differences in the detectability of vessel branches between MRA and CTA, a McNemar test was performed.All angiograms were of diagnostic quality. There were no statistically significant differences between MRA and CTA for the detection of branches of the external carotid artery that are relevant host vessels for microsurgery (p = 0.118). CTA was superior to MRA if all the external carotid artery branches were included (p < 0.001).MRA is a reliable alternative to CTA in vascular mapping of the cervical vasculature for planning of microvascular reconstruction of the mandible. In the setting of whole-body MRA it could serve as a radiation free one-stop-shop tool for preoperative assessment of the arterial system, potentially covering both, the donor and host site in one single examination.
EVALuna2:14369